Effects of pre-competitional rapid weight loss on nutrition, vitamin status and oxidative stress in elite boxers - Reljic, D.; Jost, J.; Dickau, K.; Kinscherf, R.; Bonaterra, G.; Friedmann-Bette, B. (Journal of Sports Sciences, 2015)
Dietary intake, vitamin status and oxidative stress were evaluated in 17 elite male boxers. Ten of them frequently reduced body weight rapidly before competitions (Weight Loss Group) and 7 did not practice rapid weight loss (Control Group). Food record checklists, blood samples for determination of vitamin status and plasma glutathione levels were obtained during a week of weight maintenance, a pre-competition week and a post-competition week. The average dietary intakes in both groups were 33 ± 8 kcal/kg, 3.7 ± 1.1 g/kg carbohydrates, 1.5 ± 0.4 g/kg protein, 1.2 ± 0.4 g/kg fat and 2.2 ± 1.0 L water per day (excluding pre-competition week in Weight Loss Group). Energy (18 ± 7 kcal/kg), carbohydrate (2.2 ± 0.8 g/kg), protein (0.8 ± 0.4 g·kg-1), fat (0.6 ± 0.3 g/kg) and water (1.6 ± 0.6 L) consumption (P-values <0.001) and intakes of most vitamins (P-values < 0.05) were significantly reduced during the pre-competition week in the Weight Loss Group. In both groups, the intakes of vitamins A, E and folate were below recommended values throughout the three periods; however, blood vitamin and plasma glutathione levels did not change significantly. Our findings indicate a low-caloric and low-carbohydrate diet in elite boxers, regardless of participating in rapid weight loss or not. Apparently, the pre-competitional malnutitrition in the Weight Loss Group did not induce alterations in the vitamin and glutathione status.